Vialess heterogeneous skin patch for multimodal monitoring and stimulation - Hyeokjun Lee; Soojeong Song; Junwoo Yea; Jeongdae Ha; Saehyuck Oh; Janghwan Jekal; Myung Seok Hong; Chihyeong Won; Han Hee Jung; Hohyun Keum; Sangyoon Han; Jeong Ho Cho; et al. (Nature Communications)
Abstract System-level wearable electronics require to be flexible to ensure conformal contact with the skin, but they also need to integrate rigid and bulky functional components to achieve system-level functionality. As one of integration methods, folding integration offers simplified processing and enhanced functionality through rigid-soft region separation, but so far, it has mainly been applied to modality of electrical sensing and stimulation. This paper introduces a vialess heterogeneous skin patch with multi modalities that separates the soft region and strain-robust region through folded structure. Our system includes electrical and optical modalities for hemodynamic and cardiovascular monitoring, and a force-electrically driven micropump for drug delivery. Each modality is demonstrated through on-demand drug delivery, flexible waveguide-based PPG monitoring, and ECG and body movement monitoring. Wireless data transmission and real-time measurement validate the feedback operation for multi-modalities. This engineered closed-loop platform offers the possibility for broad applications, including cardiovascular monitoring and chronic disease management.